Puttable and Extendible Bonds : Developing Interest Rate Derivatives for Emerging Markets - Neftci, Salih (IMF Working Papers; Working Paper, 2003)
This paper analyzes the price stabilizing properties of puttable and extendible bonds, their potential to help develop interest-rate derivative markets, and their use by governments. Their stabilizing properties imply that, when bond prices fall, prices for puttable and extendible bonds fall by less. Their embedded options work as a cushion and replicate the trading gains from hedging long-term bonds with interest rate derivatives. These bonds can help develop interest-rate derivative markets in developing countries and eventually increase demand for long-term government bonds. Informal evidence from OECD countries suggests that these bonds were useful in the 1980s, when interest rates were volatile.